2020
DOI: 10.3390/ijerph17092981
|View full text |Cite
|
Sign up to set email alerts
|

CD44 Gene Polymorphisms as a Risk Factor for Susceptibility and Their Effect on the Clinicopathological Characteristics of Lung Adenocarcinoma in Male Patients

Abstract: Lung adenocarcinoma is a subtype of lung cancer with high morbidity and mortality. CD44 is instrumental in many physiological and tumor pathological processes. The expression of unique single nucleotide polymorphisms (SNPs) contributes to protein dysfunction and influences cancer susceptibility. In the current study, we investigated the relationship between CD44 polymorphisms and the susceptibility to lung adenocarcinoma with or without epidermal growth factor receptor (EGFR) gene mutations. This study include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Liu et al (77) genotyped the CD44 gene in DNA extracted from blood lymphocytes of patients with NSCLC and found that the rs187115 (AG+GG) genotype was a significant predictor of bone metastasis and poor survival. It is widely accepted that the detection of single nucleotide polymorphisms in CD44 and other genes would be helpful in assessing the invasion ability of tumors (78).…”
Section: Osteopontin (Opn)mentioning
confidence: 99%
“…Liu et al (77) genotyped the CD44 gene in DNA extracted from blood lymphocytes of patients with NSCLC and found that the rs187115 (AG+GG) genotype was a significant predictor of bone metastasis and poor survival. It is widely accepted that the detection of single nucleotide polymorphisms in CD44 and other genes would be helpful in assessing the invasion ability of tumors (78).…”
Section: Osteopontin (Opn)mentioning
confidence: 99%
“…CD44 molecule is expressed on HSC and regulatory T lymphocytes [4,11]. CD44 on HSC is a ligand for E-and L-selectins that maintain subpopulation of bone marrow stem cells [2,9,11]. CD44 is a receptor for hyaluronic acid [11] one of the main components of stem cell microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…Six CD44 genetic variants were checked based on the data of International HapMap Project and previous investigations 16 , 20 . Jiang et al revealed that the CD44 single nucleotide polymorphism (SNP) rs1425802 locates in the promoter region.…”
Section: Methodsmentioning
confidence: 99%